CARBON MONOXIDE POISONING: LITERATURE REVIEW - Levina, Gina (Jurnal Forensik dan Medikolegal Indonesia, 2024)
Carbon monoxide (CO) is known as a colorless, odorless, tasteless, and non irritating gas. CO produced from burning gasoline, wood, charcoal, propane, or other fuels. CO competes with oxygen to bind with Hb, forming COHb and leads to shifting the oxyhemoglobin dissociation curve to the left, reducing oxygen-carrying capacity, and oxygen release into the peripheral tissue. Tissue hypoxia due to CO induces vascular permeability and increased interstitial fluid accumulation with decreased circulating blood volume affecting multiple organs. Three clinical sequences consisted of symptoms consistent with CO poisoning, recent history of CO exposure, and elevated HbCO levels should be present in diagnosing CO poisoning. The current mainstay of CO poisoning treatment is high flow, normobaric (NBO) oxygen therapy administered as soon as possible.